Anestezjologia i Intensywna Terapia Practical aspects of the use of double lumen tubes - Tombarkiewicz, Marek; Misiołek, Hanna; Kucia, Hanna; Drużba, Katarzyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
The authors of the study have tried to assess and collect the numerous practical rules which ought to be used as a reference when choosing the kind and size of double lumen tube for use in one lung ventilation in selected surgical procedures. The rudiments of double lumen tube intubation are described, underlining use of the bronchofiberoscope. The severe respiratory and ventilatory complications connected with malplacement of the tube in the airways are pointed out.